2018
DOI: 10.1111/exd.13463
|View full text |Cite
|
Sign up to set email alerts
|

The Akkermansia muciniphila is a gut microbiota signature in psoriasis

Abstract: Psoriasis is an immune-mediated chronic inflammatory skin disease. Although its pathogenesis is not fully understood, Th17 cells and the cytokines they produce, such as IL-17, IL-22 and IL-23, play critical roles in the pathogenesis of psoriasis. Evidence has demonstrated that psoriasis has some common features, including immune responses (due to Th17 cells) and inflammatory cytokine profiles, with systematic diseases including inflammatory bowel diseases (IBDs) and obesity. Recently, studies have demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
149
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(172 citation statements)
references
References 48 publications
(52 reference statements)
10
149
0
3
Order By: Relevance
“…However, there is no clear pattern of gut microbial dysbiosis among these autoimmune diseases. The lower microbial diversity detected in our study has been reported previously for other cohorts of patients with psoriasis but not in other studies . Lower diversity in patients with autoimmune disease has also been described for rheumatoid arthritis and Crohn disease .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, there is no clear pattern of gut microbial dysbiosis among these autoimmune diseases. The lower microbial diversity detected in our study has been reported previously for other cohorts of patients with psoriasis but not in other studies . Lower diversity in patients with autoimmune disease has also been described for rheumatoid arthritis and Crohn disease .…”
Section: Discussionsupporting
confidence: 77%
“…The lower microbial diversity detected in our study has been reported previously for other cohorts of patients with psoriasis 49 but not in other studies. 50,51 Lower diversity in patients with autoimmune disease has also been described for rheumatoid arthritis 47 and Crohn disease. 46,48 On the other hand, no reduction in the microbiota diversity was detected in the case of multiple sclerosis, 52 type 1 diabetes, 13 lupus erythematosus 31 or myasthenia gravis.…”
Section: Discussionmentioning
confidence: 86%
“…Significantly reduced abundance of Akkermansia muciniphila was observed among patients with psoriasis. Similar observations have been made in case of IBD and obesity, which also share a common pathological background with psoriasis including Th 17 , Th 1 and T reg role in immune response . Moreover, it has been suggested that gut microbiota control imiquimod‐induced murine model of psoriasis skin lesions by altering the T cells response …”
Section: Methodssupporting
confidence: 70%
“…Similar observations have been made in case of IBD and obesity, which also share a common pathological background with psoriasis including Th 17 , Th 1 and T reg role in immune response. 52 Moreover, it has been suggested that gut microbiota control imiquimod-induced murine model of psoriasis skin lesions by altering the T cells response. 37 Another study inspecting psoriasis patients faecal microflora composition showed an increased abundance of phylum Firmicutes and decreased abundance of phylum Bacteroidetes.…”
Section: Psoriasis and Psoriatic Arthritismentioning
confidence: 99%
“…au identificat o diversitate microbiană redusă în cazul pacienţilor cu PS, cu o abundenţă relativă scăzută pentru Actinobacteria şi Bacteroidetes (23). Suplimentar, la pacienţii cu PS, disbioza de la nivel intestinal se caracterizează prin abundenţă redusă a Faecalibacterium praunitzii (24,25) şi a Akkermansia muciniphila (26). Huang şi colab.…”
Section: Intestinalunclassified